Peningkatan Kompetensi Bahasa Inggris dan Literasi Keuangan Siswa SMP Negeri Upuhupun melalui Program English for Daily Life and Simple Accounting - Parjolo Aritonang; Wenssy Steva Nussy; Stella Rose Que; Punggulina Andawaty Tiven (Civiliza Publishing, 2026)
This service aims to improve practical English competence and financial literacy of students of Upuupung State Junior High School, Southwest Maluku, a disadvantaged and remote area with limited access to education. The methods used are participatory learning and experiential learning through two modules: English for Daily Life (greeting, everyday vocabulary, family and village descriptions, simple transactions) and Simple Accounting and Financial Literacy (introduction to money, distinguishing needs and wants, saving, simple financial record-keeping). The activity was attended by 40 students for one month, culminating in the